2013
DOI: 10.1515/jpem-2012-0342
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of art therapy in poorly controlled youth with type 1 diabetes mellitus

Abstract: The addition of intensive art therapy for poorly controlled youth with T1DM may improve their glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…The positive effects of art therapy to decrease depression and anxiety symptoms of children and adolescents with chronic diseases were reported in many studies (8,9,28). In a study on children with chronic cancer, the findings showed that art therapy had a strong psychological support effect on overcoming and depression developed after the diagnosis until post-hospitalization rehabilitation period (28).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The positive effects of art therapy to decrease depression and anxiety symptoms of children and adolescents with chronic diseases were reported in many studies (8,9,28). In a study on children with chronic cancer, the findings showed that art therapy had a strong psychological support effect on overcoming and depression developed after the diagnosis until post-hospitalization rehabilitation period (28).…”
Section: Resultsmentioning
confidence: 95%
“…In a study on 13 Type 1 diabetic children who were aged 7-16, children were exposed to background music during glucose follow-up system session for five days; it was concluded that background music is a good potential approach for better glycemic control and better glucose levels (10). When metabolic control and art therapy studies are considered, there was a significant decline after art therapy in HbA1c levels of 29 diabetic adolescents participated in another study (9). Apart from other studies, this study revealed no significant changes in HbA1c levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using art intervention in youth with type 1 diabetes mellitus (T1DM) are limited. Nuvoli et al (11) indicated youth with T1DM created drawings reflecting images of a “sick person” and were less apt to depict a stereotypical smiling, happy image of a “healthy person.” More recently, art therapy was shown to improve metabolic control when used as a clinically integrated intervention (3,12). In addition, art has been used in diabetes camp to provide opportunity for youth to decipher the emotional aspects of diabetes in a safe, secure environment (2).…”
Section: Introductionmentioning
confidence: 99%
“…Results were a decrease in hemoglobin A1c in the intervention group compared with control so in essence it may improve glycaemic control. 13 7. To examine the effects of art and music therapy on depression and cognitive function of the elderly [n=94].…”
mentioning
confidence: 99%